A genotoxicity study on Talitrus saltator (Crustacea, Amphipoda) exposed to lead and benzo(a)pyrene. Issue 1 (1st January 2020) - Di Donato, G.; Davolos, D.; Chimenti, C.; De Matthaeis, E.
Abstract: Sandy beaches are ecosystems often subjected to a variety of pollution sources, including heavy metals and polycyclic aromatic hydrocarbons, largely due to improper human activities. The sandhopper Talitrus saltator s. l . (Montagu, 1808) typically lives on supralittoral shores where it plays an important ecological role. The purpose of this study was to investigate DNA damage levels on hemocytes of T. saltator by means of the Comet assay. Firstly, we tested the sensitivity and reproducibility of the Comet assay on hemocytes of T. saltator after in vitro exposure (1 h) to the genotoxicant methyl methanesulfonate (MMS). The data demonstrated a DNA damage (defined as % DNA tail) related to MMS exposure in a concentration-dependent manner. Next, we carried out the assay on hemocytes of T. saltator that were exposed in vivo (24 h and 7 days) to (a) lead (Pb), (b) benzo( a )pyrene (B( a )P), (c) mixtures of them. Our data on exposure to Pb or B( a )P showed DNA damage on the hemocytes of T. saltator in a concentration-dependent manner, but apparently with a non-synergistic effect of exposure to their mixtures. Our results provide a background for further studies in order to verify the applicability of Comet assay on T. saltator for assessing genotoxicity levels in sandy beaches subjected to pollution.